Żydzi w Szadku – fragmenty wspomnień - Wasilewska-Klamka, Beata (Biuletyn Szadkowski, 2012)
The paper presents results of ethnographic research on the Jewish community in Szadek. By means of interviews with persons who remember the prewar period information was collected about Jewish people living there in the 1930s, during German occupation, at the time of existence and liquidation of the ghetto, and in the post-war period – return of the survivors and the history of the synagogue and the Jewish cemetery. The picture presented in this article is made up of accounts given by Szadek’s Polish residents. Their reminiscences and descriptions of persons, places, events and situations, culture, traditions and occupations reveal emotions and attitudes towards the Jewish community and throw some light on interpersonal relations.